Un outil pour saisir les représentations sociocognitives de l’espace végétal en ville - Anne Griffond-Boitier; Sophie Mariani-Rousset; Florian Litot (Cybergeo, 2021)
Many studies agree on the positive influence of green spaces on the quality of life of city dwellers. While there is a growing awareness of the diversity of uses of green spaces in relation to the well-being they provide, the role of the green environment itself has so far attracted little attention. This paper therefore aims at a better understanding of the links between the green environment (the structures of space), the respondents' feelings (the cognitive structures) and the values associated with this environment (the social structures). It explores suitable methods for collecting socio-cognitive representations of the vegetal space. Our approach consists in transforming city dwellers into "reflexive inhabitants", by proposing to them to stroll along an urban route, take photographs and comment on them using a digital tool (by delivering their feelings, the values attributed, etc.). Several types of routes are offered (central vs. peripheral districts, etc.) in order to test different degrees of integration of the planted space into the landscape. We formulate the hypothesis that the following elements influence positively the feelings: the importance of the views on the vegetation (perspectives...), the "small vegetation" (flowerpot...), the good knowledge of the places visited, the habit of a proximity to nature via one's place of residence, one's geographical origins or the practice of gardening... Conversely, negative feelings are more related to an environment that clashes with the vegetation (noise, waste, etc.) than to specific vegetation. And finally, the large size of the planted areas does not imply that they are seen or appreciated. This article does not (yet) provide analytical results, but proposes a survey protocol for collecting individual or collective representations of the planted space in urban environments.